(untitled) (World Economics and Finance Bulletin, 2023)
The collection and analysis of large amounts of data (big data) has become an important task for modern enterprises. In this article, we will look at the main problems faced by enterprises when collecting large amounts of data, as well as offer effective solutions to solve them. We will also discuss data collection methods, the results obtained during the research, and discuss the advantages and limitations of these solutions. In conclusion, we will summarize the results and offer recommendations for enterprises seeking to collect and use large amounts of data.